Unveiling biodiversity: The current status of marine species barcoding in Red Sea Metazoans - Carlos Angulo-Preckler; Christopher Hempel; Sofia Frappi; Kah Kheng Lim; Tullia Terraneo; Dirk Steinke; Lotfi J. Rabaoui; Francesca Benzoni; Carlos M. Duarte (Global Ecology and Conservation)
Preserving biodiversity is a global challenge. Censuses of marine biodiversity are indispensable for monitoring the responses of marine life to environmental changes induced by human activities. Ongoing extinction events affect both species and populations amid unprecedented environmental changes induced by climate shifts and habitat degradation. These changes result in substantial declines in biodiversity. In addition, our understanding of oceanic life remains incomplete, especially regarding elusive, rare, delicate, or understudied organisms. One example for this is the biodiversity of the Red Sea which remains largely unexplored and poorly understood. In an attempt to evaluate the current status of known versus COI-barcoded marine animal species in the Red Sea we used online taxonomic and genetic databases to provide a comprehensive analysis of the region's described marine life, focusing on the occurrence data of marine animal species to identify disparities in COI barcoding coverage at the phylum level. Our analysis reveals that barcoding coverage varies significantly among phyla, with Nematoda, Platyhelminthes, Bryozoa, and Porifera being highly underrepresented compared to Chordata. While over 6000 metazoan species from 22 phyla are known to inhabit the Red Sea, only 49.77 % appear to be barcoded. COI barcoding helps preserve biodiversity by providing a reliable and standardized method for accurately identifying and monitoring species, including those that are cryptic or newly discovered, thereby informing and enhancing conservation efforts and guiding future research efforts toward understudied regions and organisms.